Employing the Physicochemical, Spectroscopy, Antimicrobial and Antifungal Efficacy Studies of P-Hydroxy Acetophenone Based Azo Schiff Base Complexes - Wurood Ali Jaafar (Journal of Global Pharma Technology, 2018)
The azo Schiff base [Reaction of 4-aminoanypyrine and P-hydroxy acetophenone] and O-Phenylene diamine have been prepared. One azo Schiff base chelate of Co(Il), Ni(II), Cu(II) and Zn(II)ion was also prepared. The chemical frameworks of the azo Schiff base and like elemental analyses (CHN), determinations of molar conductance, 1 H &13C NMR, IR mass and electronic spectroscopy .The elemental analyses exhibited the combination of [L: M] 1:1 ratio. Established on the values IR spectral, it is showed that the azo Schiff base compound acts as neutral hexadentate ligand bonded with the metal ion from two hydroxyl, two azomethine and two azo groups of the azo Schiff base compound in chelation was confirmed by IR , 1Hand 13CNMR spectral outcomes. The UV-Vis spectral values appeared the existence of π→π* (phenyl ring), n→π* (N=N, -OH and HC=N) and an octahedral structure was suggested for the coordinate. The mass spectral outcomes assured the purity of the ligand. Furthermore, the antimicrobial and antifungal efficacy results revealed that the metal complexes were found to be more active than the free ligand. In general the activity order of the synthesized compounds can be represented as Fe (II) > Cu (II) > Ni (II) > Zn (II) > Co (II) > L. Keywords: Azo Schiff base, P-hydroxy acetophenone, antifungal efficacy, Spectroscopy.